Thermo-chemical pretreatment and enzymatic hydrolysis for enhancing saccharification of catalpa sawdust. (April 2016) - Jin, Shuguang; Zhang, Guangming; Zhang, Panyue; Li, Fan; Fan, Shiyang; Li, Juan
Highlights: Catalpa sawdust structures by four thermo-chemical pretreatments were compared. Solubilization of cellulose, hemicellulose and lignin were examined. Optimal factors were 160 °C, 3 min and 1.75% (w/v) Ca(OH)2 for reducing sugar yield. Thermo-Ca(OH)2 pretreatment is a promising method for catalpa sawdust enzymolysis. Abstract: To improve the reducing sugar production from catalpa sawdust, thermo-chemical pretreatments were examined and the chemicals used including NaOH, Ca(OH)2, H2 SO4, and HCl. The hemicellulose solubilization and cellulose crystallinity index (CrI) were significantly increased after thermo-alkaline pretreatments, and the thermo-Ca(OH)2 pretreatment showed the best improvement for reducing sugar production comparing to other three pretreatments. The conditions of thermo-Ca(OH)2 pretreatment and enzymatic hydrolysis were systematically optimized. Under the optimal conditions, the reducing sugar yield increased by 1185.7% comparing to the control. This study indicates that the thermo-Ca(OH)2 pretreatment is ideal for the saccharification of catalpa sawdust and that catalpa sawdust is a promising raw material for biofuel.